Children and video games : association with aggression, addiction and school grades. - Teo, Linda Lay Ching. (2010)
Video games pervade the lives of children. With the video games gaining their popularity amongst Singaporean children, it is crucial to assess their effects. The purpose of this research is to examine the impact of video games on children in relation to physical and relational aggression, prosocial behavior, addiction and school grades. Three hundred and thirty three children aged 8-12 years from two primary schools were selected by their teachers to participate in this study. A series of questionnaires using Danforth's Engagement-Addiction (II) scale, Huesmann and Guerra's Normative Beliefs about Aggression scale and Crick's Teacher-Reported Aggression andProsocial scale were provided to the children and their teachers.